Evaluating the Impact of the Tolerance Village Initiative on Interfaith Harmony: A Case Study in Jamika, Bandung - Nurjannah, Nurjannah; Bin AB Rahim, Muhammad Nazmi (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
The concept of "Kampung Toleransi" (Tolerance Village) is becoming increasingly significant in Indonesia as a strategy to promote ethnic, religious, and cultural diversity. This study explores the implementation of the Kampung Toleransi initiative in Jamika Village, Bojongloa Kaler District, Bandung City, which serves as a model for fostering interfaith harmony. A qualitative descriptive approach was employed, involving observations, in-depth interviews with community and religious leaders, and documentation analysis. The results indicate that Kampung Toleransi has successfully promoted interfaith harmony through diverse social and religious programs, educational initiatives, and economic activities. However, challenges such as funding constraints, scheduling conflicts among religious activities, and external threats from radical ideologies remain. The study concludes that enhancing community participation and improving coordination can further strengthen the sustainability of Kampung Toleransi. These findings offer valuable insights for replicating this model in other diverse communities across Indonesia.